Identification of signal quality around UiTM main campus / Muhammad Aizzad Mushaimi - Mushaimi, Muhammad Aizzad (2010)
As 3G networks are becoming commercially available all over Malaysia, all of the network providers compete to serve their customer with a good quality and stable network. This project is to analyze the 3G's signal quality and strength that are provided by Maxis Sdn. Bhd around targeted area at UiTM Shah Alam. The collected data from the drive test by using NEMO outdoor network scanner was plotted using Microsoft Excel. The parameters that been focused for this project are Received Signal Code Power (RSCP) which relates to signal strength and Carrier to Noise Density ratio (Ec/No) that are representing the cell quality of the pilot channel (CPICH).[3] Based from the graph obtained, we can see the relationship between each of the parameters that are being investigated.